Towards Implying Universal Design In Architectural Education In Egypt - Mai Ahmed (Journal of Architecture, Art & Humanistic Science, 2022)
Each design has the possibility either to imply or eliminate users. Universal Design (UD) asserts to grasp the user variety in ages, abilities, types, needs, and aspirations. Furthermore, it aspires to create a universally designed learning environment that allows all users of educational facilities to learn and participate. UD is a holistic approach, not a separate course that could be learned at the colleges of Architecture and Design. Thus, architects, interior, industrial, and landscape designers have a great responsibility to provide usable, readable, accessible, and inclusive products and environments for all species of users. Hence, the significance of the UD approach and its application within the architectural education in architecture colleges, as the application of this approach imparts the creation of new architectural generations that fulfill everyone's needs and provide environments and products that accommodate everyone.The chief purpose of this research is to point out the prominence of the UD approach in Architectural Education. The interviews which were carried out by the students of the Architecture Department from Aswan University have targeted to understand the extent of students' awareness of the term of UD, principles, and its concept. The study sample was 45 students from diverse classes through the academic year 2019-2020. The interviews were done one student by one to achieve the study goals. The study outcomes pointed at that there has no sufficient integration and combination of UD in design education due to two main reasons. First, there have no separate courses that clarify the concept of UD in the curriculum of the Architecture Department of Aswan University. The second reason, the popularity of the participants who have no more ideas about the UD concept and its principles. Thus, there is a necessity to imply the UD approach in the design process in Architecture schools. Additionally, an increased need of providing products and environments which are designed and built concerning all persons.